2010
DOI: 10.1111/j.1365-2052.2010.02131.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative trait loci affecting eggshell traits in an F2 population

Abstract: Good eggshell quality is important for both table egg quality and chicken reproductive performance. Weak eggshells cause economic losses in all production steps. Poor eggshell quality also poses increased risk for Salmonella infections. Eggshell quality has been a difficult trait to improve by traditional breeding, as it can be measured only for females and it is difficult and expensive to measure. Breeding for improved shell quality may therefore benefit from the use of marker-assisted selection. In an effort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 16 publications
2
30
0
1
Order By: Relevance
“…61 The region harbouring the ADAMTS7 gene overlapped with QTLs for several traits including two for egg-shell strength and stiffness. 62 Nevertheless, since the members of this gene family are known to perform a variety of physiological roles by encoding enzymes with protease activities, the ADAMTS7 genes may have wider effects on multiple traits. 63 …”
Section: Resultsmentioning
confidence: 99%
“…61 The region harbouring the ADAMTS7 gene overlapped with QTLs for several traits including two for egg-shell strength and stiffness. 62 Nevertheless, since the members of this gene family are known to perform a variety of physiological roles by encoding enzymes with protease activities, the ADAMTS7 genes may have wider effects on multiple traits. 63 …”
Section: Resultsmentioning
confidence: 99%
“…However, the other loci have definitive effects on internal egg traits in one or two stages only. Abasht et al (2009) andTuiskula-Haavisto et al (2010) reported QTLs influencing egg traits in different stages and on different chromosomal regions, and they discussed partial genetic independence of most traits at different ages. The present study also revealed that the same trait in the different stages is regulated by multiple loci with age-related effects and those have different effect sizes contributing to the trait.…”
Section: Discussionmentioning
confidence: 99%
“…NPY is an abundant and widespread neuropeptide in the nervous system of avian species (Kuenzel and McMurtry, 1988), but we did not find any reports on the relationship between eggshell strength and the NPY gene. Tuiskula-Haavisto et al (2010) have reported that quantitative trait loci (QTLs) that affect the deformation and breaking force of eggs are found on chromosome 2. However, the position of the QTLs was distinct from the position of the NPY gene on chromosome 2.…”
Section: Discussionmentioning
confidence: 99%